The Pharmacological Treatment of Pediatric Vertigo - Pasquale Viola; Gianmarco Marcianò; Alessandro Casarella; Davide Pisani; Alessia Astorina; Alfonso Scarpa; Elena Siccardi; Emanuele Basile; Giovambattista De Sarro; Luca Gallelli; Giuseppe Chiarella (MDPI AG, 2022)
Vertigo in children is a challenging topic. The lack of dedicated trials, guidelines and papers causes inhomogeneity in the treatment of vertigo in children. Meniere's disease, migraine equivalents, vestibular neuritis, paroxysmal positional benign vertigo (BPPV), persistent postural-perceptual dizziness (PPPD) and motion sickness may affect children with various degrees of incidence and clinical severity compared to adults. Several drugs are proposed for the management of these conditions, even if their use is subordinated to the child's age. In this review, we summarize the existing evidence related to the use of drugs for this clinical condition in children as a start point for new trials, stating the urgent need for international guidelines.